Examen especial en el área de talento humano y la incidencia en cumplimiento de las normativas de la empresa eléctrica pública estratégica corporación nacional de electricidad CNEL EP unidad de negocios Santa Elena período 2014 - Delgado Cherres, Greta Armida (2016)
This research was the development of the National Electricity Company Public Electricity Corporation Strategic Business Unit EP CNEL Santa Elena, the study lies mainly in the approach to apply a special examination, with the main objective to make a special examination department Talent, this is established according to the problems How the lack of a special examination affected the implementation of regulations in the Human Resource Department of Public Utility Strategic CNEL National Electricity Corporation. E.P. Business Unit Santa Elena?. Methodological address will be guided in the use of research based on the types of research: Applied field, literature, action and descriptive where the observation techniques will be used, the survey, where the theoretical methods applied : Inductive - deductive, analytical; and empirical methods: observation and others whose support is the information obtained through primary and secondary sources supported by methods and tools of research, to develop the special examination. According to the research results the following was obtained: the analysis of the components of the COSO I, reveal a confidence level of 68.75% (MODERATE HIGH), that internal control implemented in the municipal institution are conducted properly while the risk level is 31.25% (Moderate Low), stating that not all Talent performs work properly it affects the process of the activities of the entity, but it is worth noting that the staff utility are not being met policies and regulations must also be implemented staff training plans to improve job performance and organizational growth of the institution. Keywords: Special examination, COSO I